How Can Manufacturers Promote Green Innovation in Food Supply Chain? Cost Sharing Strategy for Supplier Motivation - He, Jianhong; Lei, Yaling; Fu, Xiao; Lin, Chia-Hsun; Chang, Chih-Hsiang (Frontiers in Psychology, 2020)
In the innovation of production activities by green product manufacturing or application, food supply chain cooperation is an important method to optimize the allocation of internal and external innovation resources, strengthen their own core capabilities and achieve sustainable development of enterprises. Whether the traditional revenue sharing or cost sharing strategy is still efficient in the food supply chain cooperation aiming at green innovation attracts a lot of attention. Further research about whether the traditional cooperation contract can effectively motivate suppliers to maximize their innovation efforts is required. In this paper, the green innovation effort level parameters are designed and the constraint factor of the green preference of consumers at the market end is applied to discuss the incentive strategy of cost sharing led by manufacturers. Stackelberg equilibrium structure is utilized in the incentive model in this paper to discuss the existence of the optimal cost sharing ratio, the optimal effort level and the optimal income of green innovation cooperation in the food supply chain. The results show that when the supply is interrupted due to the insufficient stimulation of green consumption at the market demand side, manufacturers need to stimulate their green innovation efforts by sharing the cost of suppliers, and the cost sharing proportion is affected by the marginal profit coefficient of manufacturers and suppliers. When the relationship between the marginal profit of suppliers and the marginal profit of manufacturers reaches a certain threshold, manufacturers use the cost sharing contract, which can effectively stimulate the green innovation efforts of suppliers and optimize the overall income of the food supply chain.